Pengaruh Konsentrasi Sukrosa terhadap Karakteristik Susu Kacang Merah (Phaseolus vulgaris L.) Terfermentasi dengan Isolat Lactobacillus rhamnosus SKG34 - Puspa Handayani, Luh Komang; Nocianitri, Komang Ayu; Suparthana, I Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
This research aims to identify the effect of sucrose concentration on the characteristics of fermented red bean (Phaseolus vulgaris L.) milk with isolate of Lactobacillus rhamnosus SKG34 and knowing the right amount of sucrose concentration to produce fermented red bean milk as probiotic drink with the best characteristics. This research used a completely randomized design (CRD) with concentration of sucrose as the main factor which consists of 6 levels including 0%, 2.5%, 5%, 7.5%, 10%, and 12.5%. The treatment was repeated 3 times to obtain 18 experimental units. The data were analyzed by analysis of variance (ANOVA) and if the treatment had a significant effect (P<0.05) on the observed variables, it was continued with Duncan New Multiple Range Test (DNMRT). The results showed that the treatment of sucrose concentration had a significant effect on the total LAB, total sugar, total acid, pH, preference value for taste, aroma, texture, sweet and sour taste score, and overall acceptance of fermented red bean milk but had no significant effect to the value of color preference. The 10% sucrose concentration produced a fermented red bean milk with the best characteristics that including the criteria for total LAB 11.54 Log CFU/ml, total sugar 14.72%, total acid 0.57%, pH value 4.67, the color was liked, taste sweet and slightly sour were liked, the aroma was slightly liked, slightly thick texture and overall acceptance were liked.